Persepsi Masyarakat terhadap Transportasi Publik Trans Sarbagita di Provinsi Bali - Ni Made Firayanti Pratiwi; Luh Indrayani; Kadek Rai Suwena (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
This study aimed at determining public perceptions towards the existence of Trans Sarbagita public transportation. The type of the research was descriptive study with a qualitative approach to describe the public perception of Trans Sarbagita public transportation in the Bali Province. The population in this study were all people living in the Sarbaguta Region with a sample of 400 respondents who were searched using the Slovin formula.Data collection methods used were questionnaires and interview. The data analysis technique used in this research is descriptive analysis. Based on the results of the study, public perceptions of the performance dimension gained a score of 10,238 which categorized as good. The service dimension was categorized as good since it received a score of 5,850 . The reliability dimension obtained a score of 5,777 which considered as good. The dimensions of product characteristics earned a score of 2,988 it was categorized as good. Dimensions of conformity with specifications was categorized as good. It obtained a score of 2,819, while the dimensions of the results obtained a score of 5,075 which categorized as below average.